2017
DOI: 10.2989/1814232x.2017.1363818
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the invasion of South African waters by the European shore-crabCarcinus maenas

Abstract: The European shore-crab Carcinus maenas has been present in South Africa since 1983. Despite this species' international reputation as a biological invader, its distribution in this region has only been considered by three outdated 'snapshot surveys.' The present study is the most comprehensive to date, providing an update on the species' range and the first temporal assessment of its abundance and demographics. Along South Africa's Cape Peninsula and surrounding areas, C. maenas was absent from 12 intertidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…9;Hampton and Griffiths 2007). In South Africa, its distribution is restricted to two harbours on the Cape Peninsula- Table Bay and Hout Bay (Mabin et al 2017). Between 2015 and 2016, a pilot management programme was conducted in Hout Bay harbour, as part of a PhD project on C. maenas.…”
Section: Marine Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…9;Hampton and Griffiths 2007). In South Africa, its distribution is restricted to two harbours on the Cape Peninsula- Table Bay and Hout Bay (Mabin et al 2017). Between 2015 and 2016, a pilot management programme was conducted in Hout Bay harbour, as part of a PhD project on C. maenas.…”
Section: Marine Invertebratesmentioning
confidence: 99%
“…Between 2015 and 2016, a pilot management programme was conducted in Hout Bay harbour, as part of a PhD project on C. maenas. The results of the surveys suggested that although eradication may be feasible if sufficient management effort was to be applied, C. maenas is not spreading outside harbours, or into undisturbed habitats (Mabin et al 2017). No further control is planned for this species.…”
Section: Marine Invertebratesmentioning
confidence: 99%
“…Studies from the Netherlands and Wales independently observed the appearance of ovigerous females between March and April [3,5], and observations from the Netherlands found that there are two windows in which ovigerous females are prevalent-during November and December, and during the spring and early summer [3]. At a site on the southwest coast of Ireland, there were two reproductive events annually, a primary winter cycle in which the larger crabs reproduced and a secondary summer cycle when smaller crabs reproduced [200]. It is possible for the same female to be ovigerous in more than one season, both because one fertilization event can yield two clutches for a female C. maenas [3] and because females carry their eggs for several months, depending on the water temperature [8].…”
Section: Ovigerous Females and Egg Releasementioning
confidence: 99%
“…The minimum size of sexually mature C. maenas varies considerably with no specific trend evident. It also should be noted that physiological maturity precedes morphological maturity [200]. In the native range the greatest minimum size of sexually mature C. maenas males is given as 44 mm in Norway [189], South Wales [5], UK [192] and Belgium [188] whereas the smallest sexually mature males (27 mm) have been reported from Portugal, many kilometers to the south [193,195].…”
Section: Size At Sexual Maturitymentioning
confidence: 99%
See 1 more Smart Citation